A influência do capacitismo no Decreto n° 10.502/2020 e no texto da PNEE 2020 (Educação e Pesquisa, 2023)
The fight for the inclusion of persons with disabilities in Brazilian regular schools intensified when Brazil ratified the Convenção Internacional sobre os Direitos das Pessoas com Deficiência and issued the Lei Brasileira de Inclusão. However, the struggle for advancements and improvement in the Brazilian inclusive teaching system retreated after the Política Nacional de Educação Especial: Equitativa, Inclusiva e com Aprendizado ao Longo da Vida (PNEE 2020) was established by Decreto n° 10.502/2020. The reason is that it proposed significant changes in the conception of inclusive education when it considered the possibility of special education services, centers, or schools to meet specific disabilities, determining that students and/or their families would be free to choose between an inclusive, regular, or bilingual school. The normative instruments were compared, and a policy segregating students with disabilities in the school environment is hidden between the lines under this alleged right. Such policy is discriminatory and ableist as it reproduces the notion that, according to a hierarchical corponormativity paradigm, these students are inferior, thus, conceiving that they are excluded from regular school due to their disabilities. Even though Decreto n° 11.370/2023 revoked Decreto n° 10.502/2020, the discussion proposed here remains relevant, considering the need to effectively implement inclusive education in Brazil.